Tuberculosis in patients with systemic lupus erythematosus. - Feng, P H (1982)
Tuberculosis associated with systemic lupus erythematosus (SLE) was studied in a cohort of 311 patients seen between 1963 to 1979. There were 16 such patients, giving rise to a prevalence rate of 5%. The characteristics of SLE-associated tuberculosis include a high incidence of miliary and far-advanced pulmonary disease, delay in establishing diagnosis, especially the extrapulmonary form, and tendency to attribute symptoms like fever, malaise, and weight loss to the lupus process. Treatment was successful in 9 patients. Of the 7 death 5 were attributed directly to the mycobacterial infection and 2 to complications of SLE.